Reliability and structural validity of an assessment of occupational value - Eakman, Aaron M., author; Eklund, Mona, author; Informa Healthcare, publisher (Colorado State University. Libraries, 2011)
This study evaluated the psychometric properties of the American English (Am. Eng.) version of the Occupational Value Assessment with predefined items (OVal-pd). The OVal-pd is a 26-item Likert-like questionnaire designed to assess the construct of occupational value as framed within the Value and Meaning in Occupations model (ValMO). Following a translation from the Swedish OVal-pd, 277 randomly selected graduate and undergraduate students from a public university in the northwestern United Stated completed the Am. Eng. OVal-pd. Test-retest and internal consistency reliability coefficients were very good utilizing an improved 22-item version of the OVal-pd. The structural validity of the 22-item Am. Eng. OVap-pd was partly confirmed through exploratory factor analysis. The scale was found to assess a one-dimensional value construct supporting the ValMO model, consisting of components clearly reflective of self-reward and concrete value. Exploratory factor analysis results were equivocal with regard to the symbolic dimension of the ValMO model as assessed by the OVal-pd. Discussion suggests the refinement of both the OVal-pd and ValMO model in the light of present and related empirical findings.
Structural validity of the Am. Eng. OVal-pd
Final, peer-reviewed manuscript.
Keywords: meaningful occupation; occupational therapy; human activity; instrument development